2019
DOI: 10.1111/bjop.12362
|View full text |Cite
|
Sign up to set email alerts
|

Evidence from masked‐priming that initial identification of brand names is via abstract letter identities

Abstract: Although visual-word recognition is often assumed to proceed on the basis of caseinvariant letter representations, previous research has shown a role for letter-case in recognizing brand names. One recent study reported early effects of letter-case in a brand-decision task using masked primes (Perea et al., 2015, British Journal of Psychology, 106, 162). The present study attempts to replicate this finding using brand names typically presented in all lowercase (e.g., adidas), all uppercase (e.g., IKEA), or ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 42 publications
(100 reference statements)
0
6
0
1
Order By: Relevance
“…However, none of the leading visual word recognition models currently addresses whether brand names are identified just as common words. One reason for this is that research on brand name identification has been extremely scarce (see Gontijo et al, 2002; Gontijo & Zhang, 2007; Martin & Davis, 2019; Perea et al, 2015, 2021, for exceptions). Thus, examining the similarities and differences between recognizing brand names and common words has important implications for a comprehensive visual‐word recognition model.…”
Section: Introductionmentioning
confidence: 99%
“…However, none of the leading visual word recognition models currently addresses whether brand names are identified just as common words. One reason for this is that research on brand name identification has been extremely scarce (see Gontijo et al, 2002; Gontijo & Zhang, 2007; Martin & Davis, 2019; Perea et al, 2015, 2021, for exceptions). Thus, examining the similarities and differences between recognizing brand names and common words has important implications for a comprehensive visual‐word recognition model.…”
Section: Introductionmentioning
confidence: 99%
“…In a brand name decision task, for brand names tthat are usually written in the lowercase format (e.g., adidas), they reported that priming was reduced when the masked identity prime was in the unfamiliar format (ADIDAS-adidas) than in a familiar format (e.g., adidas-adidas) 4 . A more recent study by Martin and Davis (2019) did not replicate this specific result but found a main effect of prime case with participants responding fastest to all brands when preceded by identity primes presented in titlecase (e.g., Adidas-adidas, Audi-Audi, Honda-HONDA). The authors noted that their interpretation that participants exploit title case format to make brand name decisions is similar in many respects to the orthographic cue hypothesis proposed by Peressotti et al (2003).…”
Section: Discussionmentioning
confidence: 75%
“…4Martin et al (2019) noted that what Perea et al (2015) described as “brand names which are usually written in the lowercase format” in fact contained both brand names like adidas and brand names usually written in title case such as Ford, Audi, and Lipton.…”
mentioning
confidence: 99%
“…Однако проблема качества записи данных, связанная с техническими ограничениями оборудования и самих методов, а также с недостаточным развитием методологии интерпретации результатов, остается актуальной. Применение в нейромаркетинге замаскированного прайминга -новое направление не только для российской, но и для мировой науки [Martin, Davis, 2019].…”
Section: сенсорный маркетинг и нейрофизиологические методы изучения поведения потребителей: основные теоретические аспектыunclassified